2019
DOI: 10.3233/nre-192779
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and normative values of the Wheelchair Propulsion Test: A preliminary investigation

Abstract: BACKGROUND: Normative data for the equivalent of gait speed via the Wheelchair Propulsion Test (WPT) do not exist for wheelchair users. OBJECTIVE:The purposes of the current study were to: 1) determine the reliability of the WPT, 2) propose and compare normative values for the WPT for young adult males and females utilizing three different propulsion techniques, and 3) compare how different wheelchair types affect performance on the WPT. METHODS: 50 young adults (25 of each sex) performed the WPT using three d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Although, there is little research to compare the obtained results, it seems that the greater progress was obtained by the study participants using the active wheelchairs. The results of the Andrews study confirmed that the wheelchair type influence the propulsion technique [ 39 ] and so it can influence the performance improvement.…”
Section: Discussionmentioning
confidence: 95%
“…Although, there is little research to compare the obtained results, it seems that the greater progress was obtained by the study participants using the active wheelchairs. The results of the Andrews study confirmed that the wheelchair type influence the propulsion technique [ 39 ] and so it can influence the performance improvement.…”
Section: Discussionmentioning
confidence: 95%